Liver immunology and its role in inflammation and homeostasis - Mark W. Robinson; Cathal Harmon; Cliona O’Farrelly (2016)
The human liver is usually perceived as a non-immunological organ engaged primarily in metabolic, nutrient storage and detoxification activities. However, we now know that the healthy liver is also a site of complex immunological activity mediated by a diverse immune cell repertoire as well as non-hematopoietic cell populations. In the non-diseased liver, metabolic and tissue remodeling functions require elements of inflammation. This inflammation, in combination with regular exposure to dietary and microbial products, creates the potential for excessive immune activation. In this complex microenvironment, the hepatic immune system tolerates harmless molecules while at the same time remaining alert to possible infectious agents, malignant cells or tissue damage. Upon appropriate immune activation to challenge by pathogens or tissue damage, mechanisms to resolve inflammation are essential to maintain liver homeostasis. Failure to clear 'dangerous' stimuli or regulate appropriately activated immune mechanisms leads to pathological inflammation and disrupted tissue homeostasis characterized by the progressive development of fibrosis, cirrhosis and eventual liver failure. Hepatic inflammatory mechanisms therefore have a spectrum of roles in the healthy adult liver; they are essential to maintain tissue and organ homeostasis and, when dysregulated, are key drivers of the liver pathology associated with chronic infection, autoimmunity and malignancy. In this review, we explore the changing perception of inflammation and inflammatory mediators in normal liver homeostasis and propose targeting of liver-specific immune regulation pathways as a therapeutic approach to treat liver disease.